Optical Fiber Communication Conference (OFC) 2021 2021
DOI: 10.1364/ofc.2021.w1c.4
|View full text |Cite
|
Sign up to set email alerts
|

2D Grating Coupler Induced Polarization Crosstalk in Coherent Transceivers for Next Generation Data Center Interconnects

Abstract: We investigate fundamental properties of polarization-splitting/combining 2D grating couplers for silicon photonic coherent transceivers. Linear cross-polarization related polarization crosstalk causes signal non-orthogonality. The relevance of these effects is illustrated in a 16-QAM experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Here, we extend the work from Ref. [24] in several aspects. First, we provide a more comprehensive study on polarization related parameters of 2D GCs, namely, the polarization split ratio and the polarizations' angular relation.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Here, we extend the work from Ref. [24] in several aspects. First, we provide a more comprehensive study on polarization related parameters of 2D GCs, namely, the polarization split ratio and the polarizations' angular relation.…”
Section: Introductionmentioning
confidence: 58%
“…All 2D GCs have a coupling angle ϑ = 8 • at the symmetry plane. Below, we begin with conventional designs, as those used in our previous work [24].…”
Section: Evaluation Of 2d Grating Couplers For C-and O-bandmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, with the procedure outlined in Ref. [31], we found that the out-coupled 2D GC signals from the two arms are 95°-polarized to each other at 1550 nm.…”
Section: C-band A-si:h 2d Gcs At the Metal2 Levelmentioning
confidence: 82%
“…spot-size converters (SSC), should be implemented. The additional use of polarization rotator-splitter would also allow for an efficient realization of dual polarization coherent receivers, avoiding concerns regarding the non-orthogonality of 2-dimensional GRCs [19]. The use of SSCs would not only improve the coupling efficiency, but also open the device to communication links from O-to L-band.…”
Section: A Optical Interface and 2 × 2 MMI Networkmentioning
confidence: 99%